A randomized trial comparing two approaches to weight loss: Differences in weight loss maintenance. (February 2014) - Carels, Robert A; Burmeister, Jacob M; Koball, Afton M; Oehlhof, Marissa W; Hinman, Nova; LeRoy, Michelle; Bannon, Erin; Ashrafioun, Lee; Storfer-Isser, Amy; Darby, Lynn A; Gumble, Amanda
This study compared treatment outcomes for a new weight loss program that emphasized reducing unhealthy relationships with food, body image dissatisfaction, and internalized weight bias (New Perspectives) to a weight loss program that emphasizes environmental modification and habit formation and disruption (Transforming Your Life). Fifty-nine overweight and obese adults (body mass index ≥ 27 kg/m 2 ) were randomly assigned to either a 12-week New Perspectives or Transforming Your Life intervention. Despite equivalent outcomes at the end of treatment, the Transforming Your Life participants were significantly more effective at maintaining their weight loss than New Perspectives participants during the 6-month no-treatment follow-up period.